Evaluasi Fungsi Dewan Perwakilan Rakyat Dalam Proses Legislasi Tinjauan Dari Perspektif Konstitusi - Gradensia Ardiani Ida; Saryono Yohanes; Yonas S.O. Benu (Journal of Innovative and Creativity (Joecy), 2026)
This study aims to analyze the legislative function of the House of Representatives (DPR) in the law-making process from a constitutional perspective and to identify the challenges affecting its effectiveness. The research employs a normative juridical method using statutory, conceptual, historical, and analytical approaches. Data were collected through library research involving primary, secondary, and tertiary legal materials and analyzed using descriptive qualitative techniques. The findings indicate that, normatively, the DPR has carried out legislative procedures in accordance with the 1945 Constitution of the Republic of Indonesia and Law Number 12 of 2011 as amended. Nevertheless, its implementation continues to face significant challenges, including low legislative quality and productivity, the dominance of political interests over public interests, and limited public participation in the legislative process. Therefore, strengthening a legislative mechanism that is transparent, accountable, participatory, and responsive to public interests is essential to produce high-quality legislation and to uphold the principles of a democratic constitutional state.